Comparison of measured and estimated height in the elderly with different functional classifications - Kristine Jansen, Ann; Denise Angela Gonçalves dos Santos,; de Oliveira Ramiro, Déborah; Ribeiro dos Santos, Rodrigo (O Mundo da Saúde, 2020)
One of the effects of aging on the body is the reduction of height, which may overestimate the body mass index (BMI). It is hypothesized that frail elderly people are more affected by this decline in height, however this is not clear in the literature. The aim of this study was to compare the measured and estimated height and the BMI derived from measured and estimated measurements, in the elderly according to the functional classification. A cross-sectional study with secondary data was carried out with elderly people in outpatient care, classified as robust, at risk of fragility, and fragile. Estimated height was calculated from knee height and estimated BMI with the estimated height. In the statistical analysis, ANOVA test and the Hochberg's GT2 test were applied, when comparing the 3 categories of functionality. The sample consisted of 116 elderly people with a mean age of 83.6 (8.5), mostly women 73.0 (62.9%), and classified as robust 54.0 (46.6%). The difference found for height was 4.2 (5.2), 4.6 (4.9), 7.1 (5.3) cm respectively for the robust, at risk of fragility, and fragile. The difference between the robust and the fragile was significant (p=0.033). A similar result was obtained by assessing the difference between BMIs (p=0.019). The study showed that frail elderly people have greater differences between measured and estimated height, in comparison with robust people, suggesting that frail elderly people have more height impairment, which can directly impact nutritional diagnosis. Caution is suggested in the use of measured height in the elderly, particularly in the frail.